Development of High Order Thinking Skills Based Assessment Tools in Pancasila Course: Critical Digital Citizenship Oriented - Triyani Triyani; Maryam Mustika; Sakman Sakman; Herry B Mantir (Jurnal Lingua Idea, 2021)
The purpose of this research and development is to develop a HOTS-based assessment tool oriented to critical digital citizenship on Pancasila as an ethical system and Pancasila as the basis for developing science and technology, namely the production of an assessment tool that focuses on higher-order thinking skills (HOTS) in students. The method used in this research is the type of development research (R&D) with stages of market needs analysis, development, testing, and product revision. The form of the implementation of this research can be described as (1) workshop on analysis of Pancasila course curriculum (learning outcomes, material substance, assessment tools that have been developed; (2) workshop on development of HOTS-based assessment tools in Pancasila courses oriented towards critical digital citizenship ; (3) FGD expert validation; (4) trial of HOTS-based assessment tool in Pancasila course is oriented towards critical digital citizenship; and (5) preparation of the final research report. The results of this research and development that is based on expert assessment (expert) to the assessment tool were developed which got a mean score of 3.6 in both categories so that used for the assessment process. Based on the results of trials and reflections on the HOTS-based assessment tool oriented to critical digital citizenship, it was found that, First, students are happier when learning uses audio-visual. Second, the learning video assessment tool makes them better understand in analyzing phenomena that occur in society related to the actualization of Pancasila values ​​in their daily lives and environment. Third, the questions contained in the video make students think critically. Fourth, this learning video makes students understand and realize that there are still many students ignorant in their actions to be able to apply the values ​​of Pancasila.